A sustainable and low-cost route to prepare magnetic particle-embedded ultra-thin carbon nanosheets with broadband microwave absorption from biowastes. (15th October 2022) - He, Xue; Peng, Hualong; Xiong, Zhiqiang; Nie, Xuliang; Wang, Dan; Wang, Guangsheng; Liu, Chongbo
Abstract: Two-dimensional (2D) carbon nanomaterials have attracted extensive attention in the field of microwave absorption (MA) owing to their unique layered structure, tailorable atomic layer, tunable active surface, and high dielectric loss. Here, novel porous graphene-like heterostructures are facilely prepared through the carbonization of pomelo peel (PP)/prussian blue (PB) and PP/PB analogues (PBA). The magnetic particles derived from PB and PBA are uniformly distributed in the N-doped carbon (NC) ultra-thin nanosheets, which enhances the magnetic loss and improves the interfacial polarization. The optimized Fe/ZnO/NC-7 sample exhibits a maximum reflection loss (RLmax ) of −58.12 dB at 2.05 mm, and an ultrabroad effective bandwidth (RL ≤ −10 dB) of 7.6 GHz is achieved at 1.9 mm, which covers nearly half of the measured frequency range. The superior MA performance of Fe/ZnO/NC-7 composite is ascribed to the unique magnetic particle-embedded carbon nanosheet, which not only optimizes the impedance matching but also enhances the electromagnetic wave (EMW) attenuation ability through 2D conductive networks and multiple polarization processes. Overall, this work offers an environmentally friendly method to prepare low-cost and high-performance microwave absorbers from biowastes, which exhibit superior application potential as compared to other 2D microwave absorbers including graphene and MXene. Graphical abstract: Image 1 Highlights: A sustainable route from biowastes to excellent microwave absorbers. The natural texture of pomelo peel and Fe catalysis is utilized to obtain ultra-thin carbon nanosheets. Magnetic particle dispersion in honeycomb-structure carbon sheet optimizes the impedance matching. The optimal RL value reaches −58.12 dB, and the broadest fe is 7.6 GHz at 1.9 mm.